An experimental and numerical study of an innovative flexural damper to improve the behavior of CBF braces - Park, Min Jae; Ghamari, Ali; Putra Jaya, Ramadhansyah (Institution of Structural Engineers, 2025)
Although the Concentrically Braced Frames (CBF) has significant advantages such as high lateral stiffness and strength, it suffer from low energy absorption capacity. The use of metallic passive energy dampers is considered an effective solution that can improve the performance of this system. Therefore, in this paper, a damper with a flexural mechanism (I-shaped and rectangular-shaped)is introduced and investigated experimentally and numerically. In this regard, the necessary equations for its design are also proposed. The experimental test revealed that with the same area section for both dampers, although the I-shaped damper pertains greater ultimate strength and stiffness by 3.65 times and 3.29 times than the rectangular damper, it has 62 % rotation capacity. Numerical results showed that by locating the damper in the middle of the diagonal member elements, the I-shaped damper has an ultimate strength of 3–10 % greater than rectangular damper whereas it reached 11–29 % when it is located at the end of the diagonal member elements. Comparing the stresses created in the damper and the diagonal element shows that by using the rectangular damper instead of the I-shaped damper, the stress in the brace element is reduced by 19 %. Correspondingly, when the damper is installed in the middle of the diagonal member element, the stress is reduced by 28 %, which is significant.